Properties and Hydrophobization of Nonwoven-Woven All-Cellulose Composites - Uusi-Tarkka, Eija-Katriina; Eronen, Eemeli; Begum, Afshan; Jänis, Janne; Kadi, Nawar; Khalili, Pooria; Skrifvars, Mikael; Heräjärvi, Henrik; Haapala, Antti (BioResources, 2024)
All-cellulose composites (ACCs) have been fabricated by using a variety of cellulosic sources, versatile technologies, and are sustainable alternatives for traditional composites. In this study, nonwoven-woven ACC laminates were created from wood-based Spinnova short fibers and Lyocell fabrics via partial dissolution and an NaOH-urea solvent system. The less-known wood-based Spinnova fiber is created for the textile industry, but it also has great potential for the composite industry. To identify the mechanical properties of ACCs—which greatly influence the range of material application—tensile, impact, and flexural tests were conducted. The mechanical properties indicated only moderate properties, which are influenced by high porosity and weak fiber bonding. Despite this, valuable information on the nonwoven-woven structured ACCs was obtained. To improve the ACC laminate’s ability to resist moisture, bio-based coatings (e.g., commercially available birch bark betulin and suberin acid mixture) were applied on the surface of ACCs and it successfully improved the wetting resistance. The results of contact angle analyses demonstrated that the highest contact angle of 128° was measured for betulin-coated laminates and the best stable hydrophobicity calculated a minute after the beginning of the experiment were observed at 109° for the uncommercial pressurized hot ethanol (PHE) extract of birch bark.